Biokomposit dari Serat Daun Nanas dan Serat Fiberglass Menggunakan Matriks dari Limbah Tutup Galon: Biocomposites of Pineapple Leaf Fiber and Fiberglass Fiber Using a Matrix of Waste Gallon Lids - Alfi Syahrin Yuliantari; Ulya Nadhatul Shifa; Arifianto Adi Wibowo; Hidayat, Arif (Chemistry Department, Universitas Islam Indonesia, 2024)
This research aims to determine the effect of matrix types with natural and synthetic fibers as composite reinforcement on the tensile and bending strength of composites. The types of matrices used are waste gallon lids while the types of fiber used are pineapple leaf fiber and fiberglass. The ratio between matrix material and reinforcing material in the sample varied. Tensile testing uses the ASTM D638 standard size while bending testing uses the ASTM C393 standard size. The overall highest tensile strength is found in pineapple leaf fiber reinforcement against gallon lid matrix with a maximum tensile stress value of 30.39 MPa at a ratio of 1:4. Meanwhile, the lowest tensile strength was found in pineapple leaf fiber against gallon lid waste with the lowest tensile stress value of 3.88 MPa at a ratio of 2:8.